Comparative Studies on the Interaction Between the Acriflavine and Bovine Serum Albumin by Fluorescence Spectroscopy, Synchronous Fluorescence - Guo, Ying; Liu, Baosheng; Li, Zhiyun; Zhang, Lihui (Asian Journal of Chemistry, 2015)
Under simulated physiological conditions, we studied the reaction mechanism of acriflavine (ACF) with bovine serum albumin (BSA) at different temperature by utilizing fluorescence quenching method and synchronous fluorescence method, respectively. The results indicate that acriflavine could quench the intrinsic fluorescence of bovine serum albumin strongly and the quenching mechanism was a static quenching process; the electrostatic force played an important role on the conjugation reaction between acriflavine and bovine serum albumin. The results obtained by the two methods were consistent, which indicated synchronous fluorescence spectroscopy can replace traditional fluorescence quenching method to study reaction mechanism of dyes with proteins.